‼️Please help‼️
Find the value of x and RT if RS=24 cm
‼️Please help‼️ Find the value of x and RT if - 1

Answers

Answer 1
Answer:

RS = RT + TS = 24 cm

Let's plug our values into the equation above

24cm = 6x - 4 + 10cm

Combine like terms

24 cm = 6x + 6 cm

Subtract 6 cm from both sides

18 cm = 6x

Divide both sides by 6

3 = x

Plug 3 into the expression for RT

RT = 6(3) - 4 = 18 - 4 = 14 cm

Similarly, we know that TS = 10 cm and RS = 24 cm

24 cm - 10 cm = 14 cm

RT = 14 cm

14 cm = 6x - 4

Add 4 to both sides

18 cm = 6x

Divide both sides by 6

3 = x


Related Questions

Which equation is represented by the graph below?O 2y + x = 10O y-2x = -5O -2y = 10x - 4O 2y = -4x - 10
PLEASE HELP ill Mark BRAINLIEST 31 points too
A space probe takes 45.215 days to travel to Mars, a distance of 60,004,000 kilometers. What is the speed of the probe in meters per second?
How do you know 37? I don't understand, do you add another line connecting it to make a whole triangle or ..I don't understand..
Bruce has a bottle that contains 60% of lemon juice and the rest water. The bottle has 1 liter of water.Part A: Write an equation in one variable that can be used to find the total number of liters of lemon juice and water in the bottle. Define the variable used in the equation. (5 points)

How to find the volume of a rectangular prism

Answers

To find the volume of a rectangle prism, you will need to use the formula V= lenght * width * height. Make sure you state your answer in cubic units.
For example you have a rectangle prism with a lenght of 15m, width 8m, and a hieght of 12m.
V = l * w * h
V = 15 * 8 * 12
V= 120 * 12
V= 1,440
V= 1,440m^3

I hope this help.

Answer:

L x W x H

Step-by-step explanation:

L=Length

W=Width

H=Height

You find your L, W, and H. Multiply your L, W, and H.

Example:

L=Length

W=Width

H=Height

L=7

W=2

H=4

7 x 2 x 4

7 x 2 = 14

14 x 4 = 56

Rearranging to check my work:

7 x 4 x 2

7 x 4 = 28

28 x 2 = 56

I was right.

Hope this answers your question.

What is the sum of all of the odd numbers from 1 to 59?

Answers

Answer:

sum = 900

Step-by-step explanation:

The sum of all odd number can be solved using arithmetic progression formula.

Odd numbers are numbers that cannot be exactly divided by 2 .That means odd number have remainder when divide by 2.

The first odd number is 1

The second is  3

The sequence goes like this

1, 3, 5, 7, 9, 11, 13, 15, 17, 19 , 21 .................................59

a = 1

d = 2

where

a = first term

d = common difference

let us find the number of terms before finding the sum

nth term = a + (n - 1)d

59 = 1 + (n - 1)2

59 = 1 + 2n - 2

59 + 2 - 1 = 2n

60 = 2n

n = 60/2

n = 30

Sum = n/2(a+L)

where L = last term

sum = 30/2(1 + 59)

sum = 15(60)

sum = 900

arith. series for odd number
An = 1 + 2(n-1) ; A1 = 1

sum to n terms
Sn = (An + A1)n/2 ;
An=59, n = 29

Suppose you buy a new car whose advertised mileage is 23 miles per gallon​ (mpg). After driving your car for several​ months, you find that its mileage is 19.4 mpg. You telephone the manufacturer and learn that the standard deviation of gas mileages for all cars of the model you bought is 1.07 mpg. A. Find the​ z-score for the gas mileage of your​ car, assuming the advertised claim is correct.
B. Does it appear that your car is getting unusually low gas​mileage?

Answers

Answer:

B.

Step-by-step explanation:

A.

mu = population mean = advertised mean = 23

x = raw score = 19.4

sigma = population standard deviation = 1.07

z = (x - mu)/sigma

z = (19.4 - 23)/1.07

z = -3.36448598130841

z = -3.36

=======================================

B.

The general rule is that if -2 \le z \le 2, then the z score is not unusual. Otherwise, it is unusual.

Since z = -3.36 falls outside the range, the car is getting unusually low gas mileage.

(3x+1)(2x-5)=39
i need help

Answers

(3x+1)(2x-5)=39 \n6x^2-15x+2x-5=39 \n6x^2-13x-5=39 \ \ \ \ \ \ \ \ \ \ |-39 \n6x^2-13x-44=0 \n6x^2-24x+11x-44=0 \n6x(x-4)+11(x-4)=0 \n(6x+11)(x-4)=0 \n6x+11=0 \ \lor \ x-4=0 \n6x=-11 \ \lor \ x=4 \nx=-(11)/(6) \ \lor \ x=4 \n\boxed{x=-1 (5)/(6) \hbox{ or } x=4}
                       (3x + 1)(2x - 5) = 39
              3x(2x - 5) + 1(2x - 5) = 39
3x(2x) + 3x(-5) + 1(2x) + 1(-5) = 39
          6x² + (-15x) + 2x + (-5) = 39
                  6x² - 15x + 2x - 5 = 39
                          6x² - 13x - 5 = 39
                                        - 39 - 39
                        6x² - 13x - 44 = 0
                                            x = -(-13) ± √((-13)² - 4(6)(-44))
                                                                    2(6)
                                            x = 13 ± √(169 + 1056)
                                                               12
                                            x = 13 ± √(1225)
                                                       12
                                            x = 13 ± 35
                                                      12
                                            x = 13 + 35    ∨    x = 13 - 35
                                                      12                         12
                                            x = 48        ∨        x = -22
                                                  12                         12
                                            x = 4         ∨         x = -1⁵/₆
The solution set us equal to {4, -1⁵/₆}.

Another one this one has two anwser first up is A

Answers

Answer:

g = 6

Step-by-step explanation:

3.8g + 8 = 1.8g + 20

Subtract 1.8g from both sides;

2g + 8 = 20

Subtract 8 from both sides;

2g = 12

Divide both sides by 2;

g = 6

You can check if the value of g is correct by plugging in the value of g to the equation. If your check does not it doesn't mean your answer is not correct because sometimes it can be a no solution equation which means that there is no solution to the equation.

Check:

3.8(6) + 8 = 1.8(6) + 20

22.8 + 8 = 10.8 + 20

30.8 = 30.8

It means its correct

What is (24 times 25)50 50=?

Answers

the answer to this is 600